Thermal conductivity, rheological behaviour and density of non-Newtonian ethylene glycol-based SnO2 nanofluids - Mariano, Alejandra Beatríz (2013)
The thermal conductivity, rheological behaviour and the high-pressure density of several non-Newtonian ethylene glycol-based SnO2 nanofluids were analysed. The thermal conductivity and density were measured at 283.15, 303.15 and 323.15K whereas rheological characterization was performed at 303.15K. Nanofluids with concentrations of SnO2 nanoparticles up to 25% in weightfraction were designed for thermal conductivity and rheological studies while density behaviour were analysed up to 5% at pressures up to 45 MPa. Thermal conductivity increases as usual with weight fraction showing an enhancement up to 14% in the range studied, and the experimental values were compared with available theoretical models. The volumetric behaviour shows a contractive behaviour and a departure from ideal behaviour, which is incremented with the concentration of the nanoparticles. The temperature and pressure dependence on this contractive behaviour is also studied. The rheological tests performed evidence shear thinning behaviour. In addition, the viscosity at a given shear rate is time dependent, i.e. the fluid is rheopectic. Finally, using strain sweep and frequency sweep tests the storage modulus, G , and loss modulus, G, were determined, showing viscoelastic behaviour for all samples, a fact that must be carefully taken into account for any application involving nanofluid flow.